2015
DOI: 10.1007/s12232-015-0240-1
|View full text |Cite
|
Sign up to set email alerts
|

Futures hedging with basis risk and expectation dependence

Abstract: This paper examines the behavior of the competitive firm under price uncertainty. The firm has access to a futures market for hedging purposes. Basis risk exists because the random spot and futures prices are not identical at the time when the futures contracts mature. We show that the firm optimally produces less in the presence than in the absence of the basis risk. We show further that the concept of expectation dependence that describes how the basis risk is correlated with either the random spot price or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Fama & French (2015) [6] found that the interest rate change, storage costs, and opportunity costs have different effects on the basis volatility for commodity futures. Broll, Welzel & Wong (2015) [7] pointed out that if the random price is negatively correlated with the expected value of the basis risk, then partial hedging is optimal; if there is a positive correlation, then excessive hedging is optimal, and the optimal position will be uncertain. Zhuang et al (2016) [8] explored the basis risk for the hedging in the steel futures market and analyzed the impact of macroeconomic factors and micromarket factors on the basis risk empirically, and it was found that the VaR of basis provides a foundation for hedging the risks with parametric, semiparametric, and nonparametric GARCH methods.…”
Section: Introductionmentioning
confidence: 99%
“…Fama & French (2015) [6] found that the interest rate change, storage costs, and opportunity costs have different effects on the basis volatility for commodity futures. Broll, Welzel & Wong (2015) [7] pointed out that if the random price is negatively correlated with the expected value of the basis risk, then partial hedging is optimal; if there is a positive correlation, then excessive hedging is optimal, and the optimal position will be uncertain. Zhuang et al (2016) [8] explored the basis risk for the hedging in the steel futures market and analyzed the impact of macroeconomic factors and micromarket factors on the basis risk empirically, and it was found that the VaR of basis provides a foundation for hedging the risks with parametric, semiparametric, and nonparametric GARCH methods.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used approach is confined to choosing only futures for hedging risk, from which two celebrated theorems (separation theorem and full-hedging theorem) emanate, see e.g., [4][5][6]). …”
Section: Introductionmentioning
confidence: 99%